2013
DOI: 10.4208/cicp.130911.121011s
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Solvent Effects on Protein-Ligand Interactions Using Fully Polarizable Continuum Model and Rational Drug Design

Abstract: This is a brief review of the computational modeling of protein-ligand interactions using a recently developed fully polarizable continuum model (FPCM) and rational drug design. Computational modeling has become a powerful tool in understanding detailed protein-ligand interactions at molecular level and in rational drug design. To study the binding of a protein with multiple molecular species of a ligand, one must accurately determine both the relative free energies of all of the molecular species in solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 153 publications
0
5
0
1
Order By: Relevance
“…The SVPE method is also known as the fully polarizable continuum model (FPCM), 2324, 2935 as it fully accounts for both surface and volume polarization effects in solute-solvent electrostatic interactions. 3637 In the SVPE procedure, 2728, 38 the solute cavity surface is defined as a solute electron-charge isodensity contour determined self-consistently during the SVPE interaction process, and the SVPE results converge to the exact solution of the Poisson’s equation with a given numerical tolerance. The converged SVPE results merely rely on the contour value at a given dielectric constant and a certain quantum mechanical calculation level.…”
Section: Methodsmentioning
confidence: 99%
“…The SVPE method is also known as the fully polarizable continuum model (FPCM), 2324, 2935 as it fully accounts for both surface and volume polarization effects in solute-solvent electrostatic interactions. 3637 In the SVPE procedure, 2728, 38 the solute cavity surface is defined as a solute electron-charge isodensity contour determined self-consistently during the SVPE interaction process, and the SVPE results converge to the exact solution of the Poisson’s equation with a given numerical tolerance. The converged SVPE results merely rely on the contour value at a given dielectric constant and a certain quantum mechanical calculation level.…”
Section: Methodsmentioning
confidence: 99%
“…The IPCM model implemented in the Gaussian program only accounts for surface polarization and completely ignores volume polarization [15,16]. It has been demonstrated that volume polarization significantly affects molecular structures [1720], properties [2123] and reactivity [24–27]. Hence, volume polarization must be accounted for in computational determination of solvent effects on the free energy barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The SVPE method is also known as the fully polarizable continuum model (FPCM) [17,1923,28,29], as it fully accounts for both surface and volume polarization effects in solute-solvent electrostatic interactions [24,30]. …”
Section: Introductionmentioning
confidence: 99%
“…the ESP charges, that fit to the electrostatic potential at points selected according to the Merz-Singh-Kollman scheme. 38b In addition, the single-point energy calculations were also carried out by using the surface and volume polarization for electrostatics (SVPE) 3943 calculations at the HF/6–31G* level, which accounts for solvent effects on such molecular descriptors as the dipole moment and HOMO/LUMO energies.…”
Section: Methodsmentioning
confidence: 99%